432 Traditional markers of myocardial dysfunction fail to detect marked reductions in physical capacity amoung chemotherapy patients. (17th January 2020) - Howden, E; Foulkes, S; Wright, L; Janssens, K; Dillon, H; Costello, B; La Gerche, A
Abstract: : Left ventricular ejection fraction (LVEF) is the current standard of care for evaluating chemotherapy-associated cardiotoxicity but changes in LVEF are poorly associated with outcomes and long-term heart failure risk. We sought to compare a more global measure of integrative cardiovascular function (VO2peak) that is strongly associated heart failure and early mortality risk with LVEF, global longitudinal strain (GLS) and cardiac biomarkers. Methods: 95 patients who were due to commence anti-cancer treatment (n = 58 anthracycline chemotherapy for breast cancer; n = 25 Bruton's tyrosine kinase inhibitor and n = 12 allogeneic stem cell transplant for haematological cancers) completed a pre-treatment and follow-up assessment within 6 months of initiating treatment. Changes in echocardiographic measures of LV function (LVEF, GLS), cardiac biomarkers (troponin and BNP) and cardiopulmonary exercise test (CPET, VO2peak) were measured. Results: Of 95 participants who underwent baseline testing, follow-up CPET and echocardiography data was available in 89 participants. LV function was normal prior to treatment (LVEF 61.5 ± 5.9%; GLS -19.4 ± 2.3) but VO2peak (23.4 ± 6.5ml/kg/min) was only 83 ± 21% (range 47-146%) of age-predicted. After treatment, we observed marked reductions in fitness (Δ-2.1 ± 3.7 ml/kg/min or -9 ± 15%, P < 0.001) which was associated with small non-clinically significant changes in LV function (LVEF Δ-2.4 ± 6.4% P = 0.001; GLS Δ-0.5 ± 1.9 P = 0.018). Troponin was increased significantly (4.0 ± 5.5 to 23.5 ± 22.5ng/ml, P < 0.001), with no change in BNP (37.5 ± 31.4 to 32.7 ± 22.0pg/ml, P = 0.87). Current diagnostic criteria for cardiac toxicity were not met in any patient despite some patients developing disabling reductions in functional capacity (VO2peak < 16ml/min/kg). Conclusion: Despite normal resting LV function prior to commencing treatment VO2peak was below age predicted. Treatment further impaired exercise cardiovascular function with minimal impact on resting measures of LV function. The assessment of cardiovascular function using CPET prior to, and following chemotherapy may be a more sensitive means of identifying patients at increased risk of future heart failure.